2018
DOI: 10.1002/pmic.201800217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Changing Ribosome Protein Compositions using Mass Spectrometry

Abstract: The regulatory role of the ribosome in gene expression has come into sharper focus. It has been proposed that ribosomes are dynamic complexes capable of changing their protein composition in response to environmental stimuli. MS is applied to identify quantitative changes in the protein composition of S. cerevisiae 80S ribosomes in response to different environmental stimuli. Using quantitative MS, it is found that the paralog yeast ribosomal proteins RPL8A (eL8A) and RPL8B (eL8B) change their relative proport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…A more plausible hypothesis is that free, extra-ribosomal RPs in axons are incorporated into pre-existing ribosomes in the axon through the replacement or addition of components. This model is consistent with recent proteomics and cryoelectron microscopy studies, which showed the presence of ribosomes lacking specific RP components in eukaryotic cells (Shi et al., 2017, Slavov et al., 2015, Samir et al., 2018). It seems possible that axonal RP synthesis plays an important role in ribosome maintenance, particularly for the surface ribosomal components that may be prone to damage (Figures 3 and S3).…”
Section: Discussionsupporting
confidence: 92%
“…A more plausible hypothesis is that free, extra-ribosomal RPs in axons are incorporated into pre-existing ribosomes in the axon through the replacement or addition of components. This model is consistent with recent proteomics and cryoelectron microscopy studies, which showed the presence of ribosomes lacking specific RP components in eukaryotic cells (Shi et al., 2017, Slavov et al., 2015, Samir et al., 2018). It seems possible that axonal RP synthesis plays an important role in ribosome maintenance, particularly for the surface ribosomal components that may be prone to damage (Figures 3 and S3).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the allocation of individual RPs was compared between cells cultivated in rich or minimal medium ( Fig. 4 D ), since previous work has highlighted changes in ribosomal stoichiometry ( 28 30 ) in changing growth environments. However, the analysis shows a highly consistent increase in all quantified RP subunits, including mitochondrial RP subunits ( SI Appendix , Fig.…”
Section: The Decreased Proteome Allocation For Amino Acid Biosynthesimentioning
confidence: 99%
“…These paralogs have highly similar, if not identical, amino acid sequences and have similar patterns of transcriptional regulation (Gasch et al 2000). Some recent studies have suggested that these paralogs can impart functional specialization (e.g., Haarer et al 2007;Komili et al 2007;Samir et al 2018;Segev and Gerst 2018). Nevertheless, while studying potential instances of such specialization it is important to keep in mind that the RP knockout collection has acquired additional mutations and duplications, which might mask or produce phenotypes (Steffen et al 2012).…”
Section: The Expression Of Ribosomal Protein Paralogs Is Differentialmentioning
confidence: 99%